Learning how to philosophize talking in Philosophy class. Experiences with texts of second grade of Bachillerato (Journal of Parents and Teachers, 2012)
The curriculum of minimums of the LOCE, the curricular corrections implemented by comunities as well as the different models of PAEG autonomous tests for the subject History of philosophy in the second grade of Bachillerato in Spain, raise us a double difficulty: once, the approach to a big number of authots and currents of time that make us reflect and update philosophical purposes, awakening the critical spirit and the reflection. In this article, we are trying to offer a current experience of texts that the students use in class, so that it is possible to implement some resources that the TIC offers aiming to create new spacies that are useful to build an agile debate and a cooperative learning that is compatible with the small school load that we have to approach the ambitious programs of the subjects.
Keywords: History of philosophy; Didactic; Clasic texts in the actuality; cooperative learning; new technologies; Google Docs; experiencies